SURG-13. EVALUATION OF 5-ALA FLUORESCENCE IN BRAIN METASTASES OF VARIOUS PRIMARY TUMORS: A MULTICENTER STUDY WITH EXPERIENCE IN 157 CASES. (12th August 2019) - Mercea, Petra Andreea; Marhold, Franz; Scheichel, Florian; Kiesel, Barbara; Mischkulnig, Mario; Berghoff, Anna; Woehrer, Adelheid; Preusser, Matthias; Knosp, Engelbert; Ungersboeck, Karl; Widhalm, Georg
Abstract: INTRODUCTION: Local recurrence of brain metastases following incomplete resection is not uncommon. One reason is insufficient intraoperative visualization of tumor tissue. Recently, visible intraoperative 5-aminolevulinic acid (5-ALA) fluorescence was reported in the first brain metastases series. Thus, the aim of this study was to investigate intraoperative 5-ALA fluorescence in brain metastases at two specialized centers in the largest patient cohort up to date. METHODS: 5-ALA was administered prior to resection of 157 brain metastases in 154 patients. Intraoperatively, the fluorescence quality (strong, vague or none) and fluorescence homogeneity (homogeneous or heterogeneous) of each brain metastasis was investigated. These 5-ALA fluorescence characteristics were correlated with primary tumor and histopathological subtype according to the current World Health Organization (WHO) 2016 criteria. RESULTS: Visible 5-ALA fluorescence was observed in 104 brain metastases (66%), whereas fluorescence was absent in the remaining 53 cases (34%).53/104 (51%) brain metastases showed strong fluorescence and 51/104 (49%) vague fluorescence. The majority of brain metastases (84%) demonstrated a heterogeneous fluorescence pattern. In context of primary tumor, visible fluorescence was less frequent in brain metastases of melanomas compared to all other tumors ( p=0.037 ). Moreover, visible fluorescence was more common for ductal breast cancer subtype than other subtypes ( p=0.008 ). CONCLUSION: Our data indicate that 5-ALA fluorescence is a valuable for intraoperative visualization of brain metastases to improve the extent of resection and thus patient prognosis. However, the frequent heterogeneous 5-ALA fluorescence pattern and lack of strong fluorescence limits the use of 5-ALA in brain metastases, claiming for further technical refinement.